2008
DOI: 10.1021/ic8003245
|View full text |Cite
|
Sign up to set email alerts
|

Li14.7Mg36.8Cu21.5Ga66: An Intermetallic Representative of a Type IV Clathrate

Abstract: Synthetic explorations in the quaternary Li-Mg-Cu-Ga system yield the novel intermetallic Li 14.7(8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Although ten clathrate types of crystal structure have been reported in the literature, the vast majority of inorganic clathrates crystallize with the type‐I structure, the types‐II, VIII, and IX being moderately represented . On the contrary, types‐III, IV, VII, and X are very rare, whereas types‐V and VI are not known among inorganic clathrates.…”
Section: Introductionmentioning
confidence: 99%
“…Although ten clathrate types of crystal structure have been reported in the literature, the vast majority of inorganic clathrates crystallize with the type‐I structure, the types‐II, VIII, and IX being moderately represented . On the contrary, types‐III, IV, VII, and X are very rare, whereas types‐V and VI are not known among inorganic clathrates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have reported the syntheses, structures, and aspects of the bonding of a series of ACs and evidence of i-QCs in the Sc-Cu-Zn, 27,28 Sc-Mg-Cu-Ga, 29 Sc-MgZn, 30,31 Ca-Au-In, 32 and Ca-Au-Ga 33 ternary systems, with the last four following our pseudogap tuning route. 29 Recently, we found that the YCd 6 -type phases also exist in the M-Au-Ge (M = Ca and Yb) systems, 34 which, for the first time, included the metalloid Ge in YCd 6 -type compounds.…”
Section: Introductionmentioning
confidence: 99%
“…During the exploratory synthesis of quasicrystals, we often encountered novel complex crystalline intermetallics with compositions nearby quasicrystals, e.g., Mg 35 Cu 24 Ga 53 , 22 Sc 4 Mg x Cu 15−x Ga 7.5 , 23 Li 14.7 Mg 36.8 Cu 21.5 Ga 66 ,24 …”
mentioning
confidence: 99%